Long time-series spatiotemporal variations of NPP and water use efficiency in the lower Heihe River Basin with serious water scarcity. (December 2016) - Yan, Haiming; Zhan, Jinyan; Yang, Huicai; Zhang, Fan; Wang, Guofeng; He, Wenjie
Abstract: It is of great significance to analyze the long time-series spatiotemporal dynamics of water use efficiency (WUE) to formulating appropriate management measures in response to the growing water scarcity in arid and semi-arid regions. This study analyzed the long time-series variations of WUE in the Lower Heihe River Basin, a typical arid and semi-arid region in China. The net primary productivity (NPP) was first estimated with the C-fix model, then WUE during 2001–2010 was calculated with the NPP and evapotranspiration (ET) data, and the accumulative WUE was further calculated. The results showed that the annual NPP and WUE in the study area ranged from zero to 448.70 gC/(m 2 a) and from zero to 2.20 gC kg −1 H2 O, respectively, both of which showed an overall increasing trend during 2001–2010. Besides, the spatial pattern of WUE kept overall unchanged during 2001–2010, but with remarkable change in some part of the study area. In addition, the accumulative WUE of the whole study area showed a first sharply decreasing and then gradually increasing trend, but there was still some scope to improve the WUE, and it is necessary to carry out some more specific policies to further improve the water allocation and WUE within the Lower Heihe River Basin. Although with some uncertainties, these results still can provide valuable reference information for improving the water resource management and ecological conservation to guarantee provision of essential ecosystem services in arid and semi-arid regions. Highlights: Long time-series NPP and water use efficiency in the Lower Heihe River Basin were estimated. Spatial patterns of NPP and water use efficiency kept overall unchanged during 2001–2010. Accumulative water use efficiency first sharply decreased and then increased. There was still some scope to improve water use efficiency. Valuable reference information was provided for water resource management and ecological conservation.